Hubungan persepsi masyarakat pesisir tentang KKLD dan partisipasi masyarakat pesisir terhadap pengelolaan KKLD Lampung Barat - Ade Suryanda; Ratna Komala; Riza Fahlevi (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2020)
Coastal and marine ecosystems are productive ecosystems. Socioeconomically, coastal communities rely heavily on the utilization of existing resources in their region. Increased coastal community activity may affect the viability and balance of future resource requirements. This research aimed to determine the relation of coastal community perception about Marine Management Area (MMA) and coastal community participation with management of West Lampung MMA. The sample of this research were 248 respondents. Sampling used convenience sampling technique. Data collection was done by using perception questionnaire and participation then analysed by prerequisite test. Prerequisite test results showed normal and homogeneous distributed data with regression equation of Ŷ = 28,478 + 0,667X. Calculation of correlation coefficient showed the value of rxy = 0.582, it means that the strength of the relationship between variables x and y was categorized as intermediate. There was a positive correlation between the perception of coastal community about MMA and the participation of coastal communities with management of West Lampung MMA.